The Pious Life of Empress Helena, Constantine the Great’s Mother, in the Light of Socrates of Constantinople and Sozomen - Bralewski, Sławomir (Studia Ceranea, 2017)
In his Ecclesiastical history, Socrates depicts Helena as a pious, strong and independent woman, the mother of the emperor, realizing her own ideas and acting as a tool in the hands of God – the ultimate inspiration of her actions. The emperor, her son, only supported her in her undertakings. According to Socrates, Helena travelled to Jerusalem to answer God’s call; there, she organized the search for the Sepulchre and the Holy Cross and found them. She was supported by Macarius, the bishop of Jerusalem, who, after God’s intervention, distinguished the True Cross from the crosses of the two villains. The empress divided the relics and sent some of them to her son to Constantinople; moreover, in the Holy Land, she built three basilicas connected with the life of Christ. Finally, Socrates mentions her piety and discusses the place of her burial. Conversely, in Sozomen’s account of the recovery of Christ’s Sepulchre and the relics, the main role is played by emperor Constantine, who wished to repay God for his blessings; he ordered the search and the construction of the basilica on Mount Golgotha. His mother only supported him in his plans, led by her devoutness, to which Sozomen pays more attention than his predecessor – he emphasizes Helena’s sensitivity to human poverty and suffering. The emperor was also involved in her generous deeds and gave her access to the imperial treasury. Thus, as indicated by Sozomen, Helena’s piety brought prosperity both to her family and to the whole Roman Empire.